Bone marrow cell therapies in ischemic cardiomyopathy. (September 2014) - Wysoczynski, Marcin; Hong, Kyung U; Moore, Joseph B
<x xml:space="preserve">Abstract</x> Decrements in ventricular function due to the permanent loss of contractile tissue remain problematic in patients with ischemic cardiomyopathy. For this reason, cell replacement therapy has received much popularity in recent years. Bone marrow is an abundant and accessible source of stem cells with regenerative potential. However, ischemic heart disease clinical trials based on bone marrow-derived stem cell (BMC) infusion have yielded discrepant results and marginal therapeutic benefits, making this modality's future uncertain. Further investigation of molecular and cellular characteristics critical for therapeutic efficacy and defining the mechanism(s) of BMC-mediated cardiac repair will be paramount for harnessing their full therapeutic potential.